Mitochondrial fatty acid oxidation deficiencies - Gregersen, Niels (Henry Stewart Talks, 2007)
Mitochondrial fatty acid oxidation (FAO) defects, FAO biochemical pathways, FAO defects, Diagnosis of FAO defects, Newborn screening for FAO defects, especially medium-chain acyl-CoA dehydrogenase (MCAD) deficiency, Diagnostic genetic analysis for MCAD gene variations, Expression studies of variant MCAD proteins in E.coli, Protein misfolding as a pathogenic mechanism in MCAD deficiency
Reviewed at 2015/09/08